1989
DOI: 10.1002/tera.1420390603
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Japanese quail embryos to o,p′‐DDT has long‐term effects on reproductive behaviors, hematology, and feather morphology

Abstract: Japanese quail eggs were injected with 1-(2-chlorophenyl)-1-(4-chlorophenyl)-2,2,2-trichloroethane o,p'-DDT(1-10 mg),1,1-bis(4-chlorophenyl)-2,2,2-trichloroethane p,p'-DDT (1-10 mg), or, in one study, 0.5 mg chlordecone dissolved in 50 microliters of corn oil on day 1 of incubation. Hatchability was not decreased by o,p'-DDT or p,p'-DDT, as compared to corn-oil-injected controls, but was reduced in progeny of parents injected in ovo with either isomer. Tremor was observed for up to 4 days posthatching only in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 37 publications
3
26
1
1
Order By: Relevance
“…To our knowledge, the present study is the first to show that eggshell thinning can be a developmentally induced effect. However, shell-less and soft-shelled eggs have been reported earlier in quail following embryonic exposure to 2-(2-chlorophenyl)-2-(4-chlorophenyl)-1,1,1-trichloroethane (o,p'-DDT) at a very high dose (about 400 mg/kg) that also reduced the number of ovipositions (Bryan et al 1989).…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, the present study is the first to show that eggshell thinning can be a developmentally induced effect. However, shell-less and soft-shelled eggs have been reported earlier in quail following embryonic exposure to 2-(2-chlorophenyl)-2-(4-chlorophenyl)-1,1,1-trichloroethane (o,p'-DDT) at a very high dose (about 400 mg/kg) that also reduced the number of ovipositions (Bryan et al 1989).…”
Section: Discussionmentioning
confidence: 96%
“…It was formerly believed that DDT and its metabolites did not possess endocrine effects, but in the 1970s and 80s several studies 18,19 suggested that DDT mimics estrogens, i.e., possessing similar pharmacological properties to β-estradiol. This gave rise to extensive investigation on the possible hormonal effects of human exposure to DDT and it byproducts.…”
Section: Health Effectsmentioning
confidence: 99%
“…Acreditava-se que o DDT e seus outros metabólitos não possuí-am efeitos endócrinos, mas no final dos anos 80 os estudos de Bryan et al 26 sugeriram que o DDT era um mimetizador de estrógenos, isto é, possuía propriedades farmacológicas semelhantes, e então começou-se a verificar o efeito hormonal da exposição ao DDT e seus derivados.…”
Section: Efeito Hormonalunclassified